Cartilage Regeneration in Full-Thickness Patellar Chondral Defects Treated with Particulated Juvenile Articular Allograft Cartilage: An MRI Analysis. (October 2017) - Grawe, Brian; Burge, Alissa; Nguyen, Joseph; Strickland, Sabrina; Warren, Russell; Rodeo, Scott; Shubin Stein, Beth
Background: Full-thickness cartilage lesions of the patella represent a common source of pain and dysfunction. Previously reported surgical treatment options include marrow stimulation, cell-based treatments, and osteochondral transfer. Minced juvenile allograft cartilage is a novel treatment option that allows for a single stage approach for these lesions. Hypothesis: Particulated juvenile allograft cartilage (PJAC) for the treatment of chondral defects of the patella would offer acceptable lesion fill rates, mature over time, and not be associated with any negative biologic effects on the surrounding tissue. Methods: A retrospective chart review of prospectively collected data was conducted to identify consecutive patients who were treated with PJAC for a full thickness symptomatic cartilage lesion. Qualitative (fast spin echo) and quantitative (T2 mapping) magnetic resonance imaging (MRI) was undertaken at the 6-, 12-, and 24-month postoperative mark. Numerous patient, lesion, and graft specific factors were assessed against MRI scores and percent defect fill of the graft. Graft maturation over time was also assessed. Results: Forty-five patients total were included in the study. Average age at the time of surgery was 26.5 years (range 13-45 years), average lesion size was 208 mm 2 (range 4-500 mm 2 ), and average donor age was 49.5 months (range 3-120 months). Sixty percent of the patients were female, while 93% of all patients underwent a concomitant procedure at the time of the index operation. Six-month MRI findings revealed that no patient-, graft-, or donor-specific factors correlated with MR scores, and 82% of the knees demonstrated good to excellent fill. Twelve-month MRI findings revealed that T2 relaxation times of deep graft demonstrated negative correlation with patient age ( P = 0.049) and donor age ( P = 0.006), the integration zone showed a negative correlation with donor age ( P = 0.026). In all, 85% of patients at 12 months displayed good to moderate fill of the graft. At 24 months, patient age demonstrated negative correlation with average T2 relaxation times of the deep and superficial graft ( P = 0.005; P = 0.0029) and positive correlation with the superficial zone of the adjacent cartilage ( P = 0.001). Donor age showed negative correlation with grayscale score ( P = 0.004) and T2 relaxation times at deep integration zone ( P = 0.018). T2 relaxation times of deep and superficial graft and integration zone improved over time ( P < 0.001) and between each time point. Conclusions: Particulated juvenile allograft tissue appears to be an acceptable reconstructive option for full-thickness cartilage lesions of the patella, offering satisfactory tissue defect fill at 6, 12, and 24 months after surgery. Imaging of the repaired cartilage demonstrates progressive graft maturation over time.